Scientific Investigation of Dyschoriste littoralis nees – A Tamil Traditional Medicinal Plant against Liver Disease - Teja, P. D. Ravi; Muthu, A. Kottai (Current Aspects in Pharmaceutical Research and Development Vol. 6, 2021)
The purpose of this study was to look into the hepatoprotective potential of Dyschoriste littoralis Nees (family Acanthaceae) on paracetamol-induced hepatotoxicity in rats. The aerial parts of Dyschoriste littoralis Nees. powder was extracted with various solvents (PE, EA and methanol) through Soxhlet extractor and crude various extracts utilized for hepatoprotective activity. The acute toxicity study was found that all the extracts are safe up to 2000mg/kg, so one tenth of this dose was consider as evaluation dose. Different extracts (Petroleum ether, Ethyl acetate and Methanol) of Dyschoriste littoralis were administered in dose of 200mg/kg/day to rats fed with high fat diet to assess its possible lipid-lowering potential Hepatotoxicity was induced by paracetamol (2g/kg b.wt.) on the 5th day of the investigational period and given orally. The activities of liver enzymes such as SGOT, SGPT, ALP, gamma-glutamyl transpeptidase (GGT), creatinine, urea, total bilirubin, total cholesterol, and triglyc in the serum of paracetamol-induced rats were enhanced. Additionally, when compared to other extracts, oral administration of the ethyl acetate extract of Dyschoriste littoralis (200 mg/ kgb.wt.) given rats significantly reduced the level of SGOT, SGPT, ALP, gamma-glutamyltranspeptidase (GGT), creatinine, urea, total bilirubin, total cholesterol & triglycerides and significantly increased the concentration of total protein and albumin. The findings suggested that the ethyl acetate extract of Dyschoriste littoralis could provide better hepatoprotective activity in rats exposed to paracetamol-induced hepatotoxicity.